Interactive feedback on extended instruments (2012)
This project aims at exploring interactivity in networked music by exploiting innovative mapping schemes to extend common musical instruments into acoustic controllers of digital sound. The sensors used were limited to only piezo element contact microphones, as they demonstrate a simple and cheap solution to retrieve an acoustic signal free of most environmental noise and crosstalk. The main idea was to employ the feedback that results from processing a particular system as a control signal, in a way that allows interaction with different musical systems by means of network communication. Another goal was to preserve the traditional techniques in which casual musicians play their instruments, so as to minimize the learning process that the creation of new interfaces require, and maximize the usability of the instruments' extensions. The extension itself is both reactive and transformative. We chose to extend the guitar and a djembe, as an example of a common ensemble of music in casual social contexts.